EVALUATING THE INFORMAL SECTOR MICRO, SMALL AND MEDIUM ENTERPRISES SOURCES OF FINANCE FOR ENTREPRENEURSHIP DEVELOPMENT IN ONDO STATE - Adebayo, Adebayo G.; E. Ojo, Oluwafemi (International Journal For Research In Business, Management And Accounting, 2021)
This study is charting a different approach to assessing sources of finance of micro, small, and medium enterprises (MSMEs) especially in Ondo State. A demonstrative data reflecting the characteristics of entrepreneurs in the state was used as a template. Simulated data items were 500 using major integrated sources of finance (MISF) as the dependent variable. This variable has four ((4) categories: 1. Government intervention which includes various empowerment and poverty alleviation programmes, giving direct financial assistance to farmers, artisans and market women; 2. Contribution/Cooperative Society includes: age grade traditional financial assistance, local and daily contribution by accredited agents, cooperative loans; 3.Personal/Business Savings includes personal savings, assistance from parents ,assistance from other relatives, plough back business profits ; 4. Micro credit/Bank loans includes credit facilities from retailers and wholesalers, traditional money lending, micro credit loans, bank overdrafts, deposit bank loans. The independent variables (predictors) are of two types based on the multinomial logistic regression model used. Three predictors are factors used in constructing the model and four predictors are covariates used to define the subpopulations only. Any independent variables (predictors) not treated as factors are under subpopulations. Factors are business experience (EXP), educational qualification (EDQ), and gender (GDR). Covariates are age of respondents (AGE), access to finance (FIN), adequacy of accounting and financial records (AFR), and type of business (BTP). Each of the predictors has different levels/categories. Findings revealed that personal/business savings was most accessed of the four categories of financial sources with 153 out of 500 and a target of 30.6%. Factors that are significant in determining sources of finance are business experience (EXP) and educational qualification (EDQ) both at 5% each. Other significant covariates are access to finance (FIN), adequacy of accounting and financial records (AFR), and the type of business (BTP) at either 1% or 5%. It can be concluded that the traditional trend in MSMEs financing has not changed. Unemployment, especially among youths, is a time bomb that the country should not take for granted It has been recommended that state governments should establish a fund to which certain amount should be transferred every year for four or five years and loan to entrepreneurs at 3% to 5% interest rates. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" /><br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />